The Impact of COVID-19 Infection on Gonadal Hormonal Functions in Iraqi Women - Kadhum, Shatha M; Mohammed, Nawar S (Journal of the Faculty of Medicine Baghdad, 2024)
Background: The COVID-19 pandemic has had effects beyond the respiratory system, impacting health and quality of life. Stress related to the pandemic has led to temporary menstrual pattern changes in around one-third of women. These changes, likely driven by stress and anxiety, can result in problematic heavy bleeding, causing anemia and negatively affecting women's well-being. This also places a substantial socioeconomic burden on individuals, families, healthcare, and society.Objectives: This study examined the impact of COVID-19 infection on the hormone levels (estradiol, prolactin, follicle-stimulating hormone, and luteinizing hormone) and heavy menstrual bleeding in Iraqi premenopausal women infected for at least four months.Methods: This case-control study was conducted from November 2021 to April 2022, involving 100 married women aged 18 to 40. Participants were divided into two groups: 50 women with heavy bleeding post-COVID-19 infection (infection duration of at least four months) and 50 non-infected women.Results: Comparing the mean ± SD of the two groups showed that the LH levels were statistically highly significant in women who suffered heavy bleeding post-COVID-19 infection compared to non-COVID-19 women, with a p-value of 0.000. There was no statistically significant difference in FSH levels between the two groups. The PRL levels were significantly higher for women who suffered substantial bleeding following COVID-19 infection compared to non-COVID-19 women, with a p-value of 0.003. Moreover, the E2 was significantly higher in women who suffered excessive bleeding following COVID-19 infection than in non-infected women.Conclusion: This study suggests that COVID-19 may temporarily disrupt menstrual patterns, possibly due to stress and anxiety affecting the hypothalamus-pituitary-ovary axis. This disruption can manifest as elevated levels of gonad hormones (LH, PRL, and E2) and, in some cases, lead to heavy bleeding after a coronavirus infection.